2011
DOI: 10.1115/1.4005375
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Potting Materials for Electronic-Packaging Survivability in Smart Munitions

Abstract: Potted electronics are becoming more common in precision-guided artillery due to demands for increased structural-robustness. In field artillery applications, the potted electronics are inactive for most of their lifetime. Projectiles may be stored in a bunker without environmental (temperature and humidity) controls for up to 20 years. In contrast, the electronics for most commercial applications tend to be active for most of their lifetime and the operating environment is more predictable. This difference ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…One drawback of this study is that the viscoelastic model employed is limited to a frequency range that falls below the vibratory frequencies the potted assembly is subjected to during gun launch (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Further studies into the highfrequency material behavior are underway to determine the impact on the material behavior and structural stability of the electronic assembly.…”
Section: Errors Andmentioning
confidence: 99%
See 4 more Smart Citations
“…One drawback of this study is that the viscoelastic model employed is limited to a frequency range that falls below the vibratory frequencies the potted assembly is subjected to during gun launch (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Further studies into the highfrequency material behavior are underway to determine the impact on the material behavior and structural stability of the electronic assembly.…”
Section: Errors Andmentioning
confidence: 99%
“…e speci�c heat varies by about 50%. Chao et al have shown that the potting would be expected to have signi�cant thermal mismatch issues based on the coefficients of thermal expansion for the potting and the ceramic chips [16]. For thermal expansion issues, ringed potting should be considered over fully potted models.…”
Section: Ermal Effectsmentioning
confidence: 99%
See 3 more Smart Citations